A High Performance Electrochemical Biosensing Platform for Glucose Detection and IgE Aptasensing Based on Fe3O4/Reduced Graphene Oxide Nanocomposite. Issue 1 (26th November 2013) - Teymourian, Hazhir; Salimi, Abdollah; Firoozi, Somayeh
Abstract A Fe3O4 magnetic nanoparticles/reduced graphene oxide nanocomposite modified glassy carbon electrode (Fe3O4/r‐GO/GCE) was further expanded into the design of a high performance electrochemical biosensing platform. First, direct electrochemistry of glucose oxidase(GOx) immobilized onto Fe3O4/r‐GO/GCE and its biocatalytic activity toward glucose oxidation was investigated. Then, differential pulse voltammetry (DPV) was used to investigate the electrochemical oxidation behavior of four DNA free bases of guanine (G), adenine (A), thymine (T) and Cytosine (C) at Fe3O4/r‐GO/GCE. In addition, a label‐free electrochemical impedance spectroscopy (EIS) method of detection was developed for Immunoglobulin E (IgE) in which the binding of IgE‐specific aptamers immobilized on Fe3O4/r‐GO/GCE leads to impedance changes associated with IgE binding events.